Stigma Towards People Living with HIV/AIDS in the Tourist Area of Batu Hiu Beach - Marisha Cheryl Angelita; Irman Somantri; Kurniawan Kurniawan (GLOBAL HEALTH SCIENCE GROUP, 2024)
The issue of HIV/AIDS does not only impacts physical health but also affects other aspects of life. One of the social impacts of this disease is the stigma received by people living with HIV/AIDS. Stigma towards people living with HIV/AIDS is one of the biggest obstacles in HIV/AIDS prevention programs, care, treatment, and support programs. Objective: This study aims to obtain an overview level of the stigma held by the community in the tourist area of Batu Hiu Beach towards people living with HIV/AIDS based on demographic charateristic. Method: This research employs a descriptive quantitative research design with a cross-sectional approach to examine the stigma in the community using a questionnaire adapted from the SHASS (Spanish HIV Stigma Scale). The population in this study consist of 750 individuals, with a sample of 261 individuals selected using the sample random sampling method. The analytical tool used is univariate. Results: Nearly the majority of respondents have a high level of stigma towards people living with HIV/AIDS (51.3%). Conclusions: The high level of stigma towards people living with HIV/AIDS indicates negative views, prejudice, and discriminatory attitudes in the community. Most respondents in this category have not received HIV/AIDS training (61.3%), have only completed primary education (69.2%), male (55%), and are in the early adulthood (65.5%) and elderly (63.6%) age groups